2016
DOI: 10.12693/aphyspola.130.688
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study for Fractional Euler-Lagrange Equations of a Harmonic Oscillator on a Moving Platform

Abstract: We investigate the fractional harmonic oscillator on a moving platform. We obtained the fractional EulerLagrange equation from the derived fractional Lagrangian of the system which contains left Caputo fractional derivative. We transform the obtained differential equation of motion into a corresponding integral one and then we solve it numerically. Finally, we present many numerical simulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…We found an oscillatory behaviour of the above thermodynamic properties modulated by quantum size effects. Similar oscillations can also be observed in other physical systems [12][13][14][15][16]. Moreover, we proved that the thermodynamic properties of Pb films cannot be correctly described using the BCS theory of superconductivity due to the strong coupling and retardation effects.…”
Section: Introductionsupporting
confidence: 78%
“…We found an oscillatory behaviour of the above thermodynamic properties modulated by quantum size effects. Similar oscillations can also be observed in other physical systems [12][13][14][15][16]. Moreover, we proved that the thermodynamic properties of Pb films cannot be correctly described using the BCS theory of superconductivity due to the strong coupling and retardation effects.…”
Section: Introductionsupporting
confidence: 78%
“…Like many other complex systems [28][29][30][31][32][33], the Eliashberg equations are too complicated to solve them in an analytical way. Due to the above, in this study the numerical analysis was performed using a self-consistent iteration methods [34], which were implemented successfully in our previous papers [35][36][37][38].…”
Section: Theoretical Model and Computational Methodsmentioning
confidence: 99%
“…For more details on the fractional derivatives and their properties, the readers can refer to [1][2][3].…”
Section: Preliminariesmentioning
confidence: 99%
“…It has been demonstrated that the fractional order representation provides a more realistic behavior of complex systems appearing in various fields of science and engineering [3]. Due to this fact, fractional calculus has some applications in chemistry [4], bioengineering [5], hydrologic modelling [6], pharmacokinetics [7], heat transfer modelling [8], viscoelasticity [9], etc.…”
Section: Introductionmentioning
confidence: 99%